ANÁLISIS DE LOS MÉTODOS NUMÉRICOS EN ECUACIONES DIFERENCIALES ORDINARIAS UTILIZANDO MATHEMATICA - JAIME SEGARRA-ESCANDÓN (Revista Ingeniería, Matemáticas y Ciencias de la Información, 2020)
In this research, the main objective is to perform the comparative analysis of numerical methods (Explicit Euler, RungeKutta 4 and LocallyExact) for the resolution of differential equations. To fulfill the purpose of this study, the system ofdifferential equations of the Lotka-Volterra model was used and the mathematical software Wolfram Mathematica wasused. To perform the comparison of the numerical methods the Lotka-Volterra model was solved using the NdSolvecommand of Mathematica, this result was compared with the Methods Explicit Euler, Runge Kutta 4 and LocallyExact. Theresults obtained from the phase diagrams and the point table of the interactions indicate that the Runge Kutta 4 methodhas greater precision, followed by the LocallyExact method. The explicit Euler method draws considerably away from theresult of NDSolve.